2015
DOI: 10.7863/ultra.34.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Blood Flow in Transjugular Intrahepatic Portosystemic Shunt Revision Using 3‐Dimensional Doppler Sonography

Abstract: Shunt volume flow measurement with 3D/4D Doppler sonography provides a potential alternative to standard pulsed wave Doppler metrics as an indicator of shunt function and predictor of revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Our observations on the use of 4D-flow MR imaging are concordant with those from a recent study on 4D Doppler US (15). These authors concluded that shunt volume measurements provide an alternative metric to quantify shunt function and that an increased shunt fraction corresponds to a decreased pressure gradient (15).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our observations on the use of 4D-flow MR imaging are concordant with those from a recent study on 4D Doppler US (15). These authors concluded that shunt volume measurements provide an alternative metric to quantify shunt function and that an increased shunt fraction corresponds to a decreased pressure gradient (15).…”
Section: Discussionsupporting
confidence: 90%
“…These authors concluded that shunt volume measurements provide an alternative metric to quantify shunt function and that an increased shunt fraction corresponds to a decreased pressure gradient (15). Future and larger studies are needed to determine whether the TIPS-to-PV flow ratio measured with 4D-flow MR imaging may be useful for predicting the risk for hepatic encephalopathy and refractory ascites and whether TIPS revision is needed due to in-stent stenosis or thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by custom algorithms implemented in MATLAB (The MathWorks, Natick, MA) through a user‐specified c‐surface by the method of surface integration of color flow–measured velocity vectors . Power mode data were used to correct for the partial volume effect …”
Section: Methodsmentioning
confidence: 99%
“…Pinter [14] revealed that during TIPS, ultrasound can dynamically detect the position of the catheter head in real time, display surrounding vascular morphology and spatial location, reduce the blindness of puncture, and improve the success rate of puncture. However, these ultrasound findings were significantly affected by ascites and intestinal gas and operator proficiency.…”
Section: Ultrasoundmentioning
confidence: 99%